LANGUAGE INTERFERENCE IN LEARNING ENGLISH OF THE SEVENTH-GRADE STUDENTS AT SMPTK IMANUEL TUAPAKAS IN SOUTH CENTRAL TIMOR REGENCY - Novriani Rabeka Manafe; Ayu Matni Pitronela Bonat; Dewi I. N. Bili Bora; Gracia M. N. Otta (Pusat Riset dan Inovasi Nasional, 2023)
The aims of this research are: (1) to identify the types of language interference in learning English, (2) to find out the most dominant example of the mother tongue in learning English, and (3) to investigate the causes of interference in learning English. The research employed a descriptive qualitative method with selected twenty students from the seventh grade as the respondents. This research used observation, interview, recording, and note-taking, for data collection while employing document analysis to analyze the gathered data. This study was conducted in the following procedure, (1) observation (2) interview (3) documentation. From the self-introduction by the respondents, the researcher found that there were three types of language interference made by seventh-grade students namely phonological, grammatical, and lexical interference. The findings also showed that the most dominant example of the mother tongue in learning English made by seventh-grade students is phonological interference. The analysis also revealed that the causes of language interference, there were students’ background and the students’ limited mastery of the English vocabulary